2011
DOI: 10.4319/lo.2011.56.3.1023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin B12 on phytoplankton growth and community structure in the Gulf of Alaska

Abstract: A majority of eukaryotic phytoplankton species require an exogenous source of vitamin B 12 for growth and recent field studies in some coastal and polar regions indicate that the addition of vitamin B 12 alone, or with another limiting nutrient can influence the accumulation of phytoplankton biomass. We quantified the concentrations and uptake rates of vitamin B 12 , characterized phytoplankton community composition, and examined the ability of vitamin B 12 to alter the growth and composition of phytoplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 43 publications
11
127
2
Order By: Relevance
“…Our field results show that because large areas in the ocean do not contain sufficient B vitamins, the efficiency of the biological pump may be controlled not only by the availability of mineral nutrients, such as Fe, N, and P, but by vitamin accessibility. Although recent field studies have confirmed the ecological importance of B 12 , because phytoplankton growth was enhanced by picomolar B 12 amendments in both coastal and open ocean environments (12,14,15,19,20), no field study has yet addressed the relevance of the other B vitamins measured in the present study. Because some bacterial groups seem to be major producers of the organic cofactors required by eukaryotic phytoplankton, B vitamins illustrate the complexity of the prokaryote/eukaryote codependency via ectocrine relationships in the marine environment.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Our field results show that because large areas in the ocean do not contain sufficient B vitamins, the efficiency of the biological pump may be controlled not only by the availability of mineral nutrients, such as Fe, N, and P, but by vitamin accessibility. Although recent field studies have confirmed the ecological importance of B 12 , because phytoplankton growth was enhanced by picomolar B 12 amendments in both coastal and open ocean environments (12,14,15,19,20), no field study has yet addressed the relevance of the other B vitamins measured in the present study. Because some bacterial groups seem to be major producers of the organic cofactors required by eukaryotic phytoplankton, B vitamins illustrate the complexity of the prokaryote/eukaryote codependency via ectocrine relationships in the marine environment.…”
Section: Resultsmentioning
confidence: 75%
“…However, those studies were mostly limited to vitamin B 12 (9)(10)(11)(12)(13)(14)(15)(16), and it is unclear whether or not those results can be extended to other essential B vitamins. The limited information that exists suggests that this is not the case (16)(17)(18)(19)(20). Only a few studies have been comprehensive enough to estimate the importance of vitamins in primary productivity and species succession, and they also have been focused mainly on the role of vitamin B 12 (19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To assess nonspecific binding and/or adsorption of the isotope a 1% gluteraldehyde ''killed-control'' bottle was also spiked with tracer and incubated along with the ''live'' bottles. A previous study (Koch et al 2012) reported that abiotic adsorption of the isotope was highest at times of low biomass and high lithogenic particle load (winter, spring). During the 2009 brown tide bloom, dead controls ranged from 3-20% of total tracer incorporation and averaged 10%, with the highest abiotic adsorption of the tracer occurring before bloom initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Since Koch et al (2012) found that uptake of both B 12 and B 1 in New York estuaries was linear over a 24 h, diel, light-dark cycle, and since that high levels of algal biomass present during incubations could rapidly alter vitamin concentrations, incubations were terminated after 2 h by filtering samples onto 0.2, 1, and 5 mm pore-size polycarbonate filters, allowing for the determination of size-fractionated uptake of the tracers. A. anophagefferens is 2-3 mm in size and dominates eukaryotic biomass during brown tides ; this study).…”
Section: Methodsmentioning
confidence: 99%